(untitled) (Journal of the Sylhet Agricultural University, 2026)
Neglected and underutilized plant species (NUPS), often referred to as future smart foods, hold immense potential for enhancing food security, nutritional diversity, and climate resilience in marginal environments. This study investigated the diversity, cultivation status, and adoption constraints of NUPS in homestead agroforestry systems at Zakiganj Upazila of Sylhet District in Bangladesh a subtropical, flood-prone region characterized by high rainfall (2,540–3,810 mm annually) and acidic soils. Using a survey-based design, data were collected through face-to-face interviews with 120 randomly selected respondents across nine unions from January to June 2025 at Zakiganj Upazila. Though the NUPS are in the verse of extinction, results revealed that still 58.3% of households cultivating them primarily due to their climate tolerance (31.7%), low input requirements (28.3%), and local availability (25.0%). Key information sources of neighbors (29.2%) and extension workers (25.0%) showed major constraints comprised of lack of knowledge (38.3%), limited seed availability (25.0%), and perceived low yields (21.7%). Only 45.8% of respondents had received relevant training. Biodiversity analysis of the seven dominant NUPS (betel nut, mulberry, bonkochu, toikor, lukluki, shaplagota, and jaralebu) showed exceptionally high diversity, with a Shannon-Weaver Index (H′) of 1.9360 (near maximum 1.9459), evenness of 0.9949, and Simpson’s Index of Diversity (1–D) of 0.8544, indicating balanced species distribution. These findings highlighted the critical and important role of traditional homegardens in conserving resilient, nutrient-dense NUPS amid a lot of climate stresses. Improving knowledge gaps, seed systems, and extension services are essential to mainstream these orphan crops, which in turn, will support dietary diversification, hidden hunger mitigation, and sustainable agriculture in the vulnerable regions of Bangladesh. J. Sylhet Agril. Univ. 12(2): 87-96, 2025